(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
The removel of parathyroid glands (PTX) decreases the development of hypertension in young spontaneously hypertensive rats (SHR) and Lyon hypertensive (LH) rats. The purpose of our study was to investigate the effect of parathyroidectomy on chronic evolution of systolic blood pressure (SBP) in young and in aged male and femele SHR rats. Our results indicate that PTX significantly reduces total plasmacalcium (mmol/L) in 6, 10, 22, and 36 weeks old male and femele rats (mean desrease: 30%, p<0.001). On the other hand, we observed that the systolique blood pressure (SBP) was lessened significantly in young and aged male SHR rats (p<0.01); nevertheless SBP was not significantly affected by PTX in femele rats. In conclusion, The inhibitory effect PTX on hypertension development is not found in femele rats, may be linked to the straightening plasma calcium level and other sex-dependant factors.